Comparative analysis of e-procurement systems - Barczak, Andrzej; Stefaniuk, Marcin (Studia Informatica. System and information technology, 2008)
In the abstract have been described basic kinds of information systems of e-procurement type. Have been showed capabilities of their utilization and advantages and disadvantages of adopted solutions. Author started discerning analysis of systems from revealing the capabilities that systems carry along during realization of bids. On the occasion of the theme there were showed conditionings and directions of development of those systems. In the following chapters of the article have been appeared other forms of e-procurement. In the first place it has been described as a system supporting, in the broad sense of the term, process of supplies in the firm, afterwords have been given advantages of enlargement of interactions’ spectrum on whole company. In the recap there were showed aspects confirming advisability of creating B2B systems, which support activity of operators in the time of market economy. In the second part of article have been showed aspects of modeling and implementation of systems under discussion. Author, step by step, will present factors, which are essential for creation of fully functional e-procurement service. Also descriptions of programming tools, used for building those applications, will be the part of aspects under consideration. Author will use a short comparison to show the best, in his opinion, tools and to present methods of their use in order to produce correctly implemented system.